1997
DOI: 10.1021/jo970985b
|View full text |Cite
|
Sign up to set email alerts
|

Copper Cyanide-Catalyzed Palladium Coupling of N-tert-Butoxycarbonyl-Protected α-Lithio Amines with Aryl Iodides or Vinyl Iodides

Abstract: Treatment of (α-aminoalkyl)lithium reagents with aryl iodides in the presence of catalytic amounts of CuCN and PdCl2(PPh3)2 or [(p-MeOC6H4)3P]4Pd affords 2-aryl substituted amines in modest to good yields. The yields can be improved by use of softer ligands such as AsPh3 and SbPh3 or by use of bis(diphenylphosphino)ferrocene (dppf). Coupled products are obtained with electron-rich aryl iodides (XArI, X = Me, OMe), and the reaction fails with electron-poor aryl iodides (XArI, X = NO2, CO2Li). Treatment of the (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…Veliparib, 6 Pradaxa, 7 and Benthiavalicarb 8 ). While important strategies for amine α-arylation have been reported by Dieter, 9 Campos, 10 Nakamura, 11 and others, 12 a generic yet mild α-arylation protocol remains largely elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Veliparib, 6 Pradaxa, 7 and Benthiavalicarb 8 ). While important strategies for amine α-arylation have been reported by Dieter, 9 Campos, 10 Nakamura, 11 and others, 12 a generic yet mild α-arylation protocol remains largely elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Dieter demonstrated that transmetalation of N -Boc-2-lithiopyrrolidine to its organocopper counterpart provides a convenient way to synthesize vinylated pyrrolidines 4,5. Using an asymmetric deprotonation methodology with the chiral base s -BuLi/(–)-sparteine6,7 to generate an enantioenriched organolithium, Dieter achieved enantioselective vinylations with er’s up to 93:7.…”
mentioning
confidence: 99%
“…Products were characterized by the comparison of their physical and spectral data with authentic samples [10,16,17,20,[25][26][27][28][29][30][31]. …”
Section: Methodsmentioning
confidence: 99%